Analisis Proses Pemecahan Masalah Matematika Berdasarkan Multiple Intelligences Siswa SMK Negeri 2 Tuban - Rachmalia Vinda Kusuma; Rita Yuliastuti (Prodi Pendidikan Matematika Universitas PGRI Ronggolawe, 2023)
This study is a descriptive study with a qualitative approach aimed at describing the process of solving mathematical problems based on students' multiple intelligences. The subjects of this study were students of class XI of SMK Negeri 2 Tuban in the odd semester of the 2022/2023 academic year. Determination of the subject resulted in four research subjects where 2 subjects represented the type of logical-mathematical intelligence and 2 subjects represented the type of visual-spatial intelligence. The research data were obtained from written tests, interviews, and multiple intelligence tests. The data analysis technique uses 4 steps, namely verbal data transcription, data reduction, data presentation, and conclusion. The results of this study explain that the visual-spatial subject completes 4 stages of problem-solving, namely understanding the problem, determining the problem-solving strategy plan, implementing the problem-solving plan, and reviewing the answers. While the logical-mathematical subject completes three stages of problem-solving, namely understanding the problem, determining a problem-solving strategy plan, and carrying out problem-solving plans.